BREAKING DORMANCY OF Casuarina equisetifolia SEED WITH LONG IMMERSION IN HOT WATER - Yopa Dwi Mutia; Muhammad Fauzan Farid Al Hamdi; Afri Rona Diyanti; Widodo Haryoko; M. Zulman Harja Utama (Jurnal Sains Agro, 2022)
Due to physical dormancy, Casuarina equisetifolia seeds have a poor germination rate, which makes it difficult to supply the seeds' needs. Soaking the seeds in hot water is a natural technique to promote water access to the seeds, especially those with a hard outer shell structure. The study's goal was to test if Casuarina equisetifolia seed dormancy could be broken by immersing them in hot water. The experiment used a completely randomized design with a long soaking treatment in hot water, which included soaking for 6 hours in normal temperature water, soaking for 6 hours with water with an initial temperature of 600C, and soaking for 12 hours with water with an initial temperature of 600C, each repeated 8 times. The observed data were subjected to a variance analysis and a F level 0.05 test. If there is a significant effect, the Honestly Significant Difference test is performed at a level of 0.05. According to the findings, breaking the dormancy of Casuarina equisetifolia seeds by soaking them in hot water for 12 hours at an initial temperature of 600C resulted in the best maximal growth potential, germination, and first count germination.